2016
DOI: 10.1016/j.drugalcdep.2015.11.020
|View full text |Cite
|
Sign up to set email alerts
|

Reductions in physical pain predict lower risk of relapse following alcohol treatment

Abstract: Objective Physical pain is considered a potential predictor of relapse in alcohol dependent individuals after treatment. The aim of this study was to evaluate whether reductions in pain level during the follow-up period after treatment were associated with lower relapse risk. Method A sample of 366 participants were recruited from alcohol treatment centers in Warsaw, Poland. At baseline information was obtained about pain level, demographics, childhood abuse, impulsivity, depressive symptoms, severity of alc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
51
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(54 citation statements)
references
References 35 publications
2
51
0
1
Order By: Relevance
“…SUD patients with both actue and chronic pain problems report more extensive drug use histories, greater severity of drug and alcohol problems, and more co-morbid psychiatric symptom sequelae than those without significant pain (Jakubczyk et al, 2015; Potter et al, 2008; Witkiewitz et al, 2015a, 2015b). Further, those in pain are less likely to attend or complete SUD treatment and reductions in pain predict lower risk of relapse following treatment (Jakubczyk et al, 2016). Co-morbidity of these conditions is also problematic due to the increasing prevalence of prescription pain medication abuse (Dworkin et al, 2007; Huang et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…SUD patients with both actue and chronic pain problems report more extensive drug use histories, greater severity of drug and alcohol problems, and more co-morbid psychiatric symptom sequelae than those without significant pain (Jakubczyk et al, 2015; Potter et al, 2008; Witkiewitz et al, 2015a, 2015b). Further, those in pain are less likely to attend or complete SUD treatment and reductions in pain predict lower risk of relapse following treatment (Jakubczyk et al, 2016). Co-morbidity of these conditions is also problematic due to the increasing prevalence of prescription pain medication abuse (Dworkin et al, 2007; Huang et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Recent preliminary findings revealed that deficits in utilizing and regulating emotions were an independent predictor of relapse in AD patients,7 whereas chronic pain was shown to be associated with worse pain-related and substance-related outcomes among adults treated for substance use disorders 13,14,72. These observations underlie the clinical significance of further studies on emotional competencies and pain in AD individuals.…”
Section: Discussionmentioning
confidence: 95%
“…Despite the importance of understanding the intersection between pain and alcohol use, only limited work has been carried out in this area and most of this has been done from a neurobiological perspective. Of clinical importance, pain is a predictor of poor drug- and alcohol-related outcomes in those treated for addictive disorders, including AUDs,12,13 and self-reported decrease in pain following treatment for AD is associated with a lower risk of alcohol relapse 14…”
Section: Introductionmentioning
confidence: 99%
“…There is concern that patients may use alcohol as a self-medication strategy to control pain or to address other associated health problems such as insomnia (Jakubczyk et al, 2016; National Institute on Alcohol Abuse and Alcoholism, 2013; Witkiewitz et al, 2015; Woodrow & Eltherington, 1988). There is evidence to support this self-medication hypothesis (Brennan, Schutte, & Moos, 2005; Riley & King, 2009), although a recent study showed that men who reported pain at baseline experienced declining alcohol use over 10 years, compared to men who did not experience pain (Bobo, Greek, Klepinger, & Herting, 2013).…”
Section: Discussionmentioning
confidence: 99%